Methadone to buprenorphine/naloxone induction without withdrawal utilizing transdermal fentanyl bridge in an inpatient setting—Azar method. (2nd November 2018) - Azar, Pouya; Nikoo, Mohammadali; Miles, Isabelle
Abstract : Background and Objectives: Although buprenorphine/naloxone is widely recognized as first‐line therapy for opioid use disorder, the requirement for moderate withdrawal prior to initiation in efforts to avoid precipitated withdrawal can be a barrier to its initiation. Methods: We present a case utilizing transdermal fentanyl as a bridging treatment to eliminate withdrawal during the transition from methadone to buprenorphine/naloxone in a patient who had ongoing significant intravenous heroin use while on methadone. Results: Patient was successfully transitioned from methadone to buprenorphine/naloxone without a period of withdrawal utilizing transdermal fentanyl as a bridge in an inpatient setting. Discussion and Conclusions: Our experience indicates a transdermal depot of fentanyl allows for slow release and elimination while buprenorphine doses are introduced during an induction without presence of withdrawal, as quantified by serial clinical opiate withdrawal score. Scientific Significance: This case report highlights ways to minimize barriers to induction of first‐line opioid substitution therapy, buprenorphine/naloxone, by eliminating withdrawal during induction phase utilizing a fentanyl bridge within the limitations of a transdermal fentanyl bridge in an inpatient setting. (Am J Addict 2018;XX:1–4)